Pregunta
upstudy study bank question image url

Decompose \( \frac{x^{3}-3 x+1}{x^{2}-x-2} \) inds its perthal frections

Ask by Clarke Beck. in South Africa
Feb 24,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The partial fraction decomposition of \( \frac{x^{3}-3x+1}{x^{2}-x-2} \) is: \[ x + 1 + \frac{1}{x - 2} - \frac{1}{x + 1} \]

Solución

We wish to decompose   (x³ – 3x + 1)/(x² – x – 2) into partial fractions. Notice that the degree of the numerator (3) is higher than that of the denominator (2), so we must first perform polynomial long division. Step 1. Divide x³ – 3x + 1 by x² – x – 2.   • Divide x³ by x² to get x.   • Multiply the divisor by x: x(x² – x – 2) = x³ – x² – 2x.   • Subtract:     [x³ + 0x² – 3x + 1] – [x³ – x² – 2x] = x² – x + 1.   • Now, divide x² by x² to get 1.   • Multiply the divisor by 1: 1 · (x² – x – 2) = x² – x – 2.   • Subtract:     [x² – x + 1] – [x² – x – 2] = 3. The quotient is (x + 1) and the remainder is 3. Therefore, we can write   (x³ – 3x + 1)/(x² – x – 2) = x + 1 + 3/(x² – x – 2). Step 2. Factor the denominator of the remaining fraction.   x² – x – 2 factors as (x – 2)(x + 1). Thus,   3/(x² – x – 2) = 3/[(x – 2)(x + 1)]. Step 3. Express 3/[(x – 2)(x + 1)] as a sum of partial fractions. Assume   3/[(x – 2)(x + 1)] = A/(x – 2) + B/(x + 1). Multiply both sides by (x – 2)(x + 1) to clear denominators:   3 = A(x + 1) + B(x – 2). Now, equate coefficients by expanding the right side:   A(x + 1) + B(x – 2) = (A + B)x + (A – 2B). Since the left side is the constant 3 (which can be viewed as 0·x + 3), we have:   Coefficient of x: A + B = 0,   Constant term:  A – 2B = 3. Solve for A and B:   From A + B = 0, we have A = –B.   Substitute into A – 2B = 3:     (–B) – 2B = 3 ⟹ –3B = 3 ⟹ B = –1.   Then, A = –(–1) = 1. Thus, the partial fractions are:   3/(x² – x – 2) = 1/(x – 2) – 1/(x + 1). Step 4. Write the final decomposition. Substitute back into the expression from the long division:   (x³ – 3x + 1)/(x² – x – 2) = x + 1 + [1/(x – 2) – 1/(x + 1)]. This is the desired partial fraction decomposition.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To decompose the expression \( \frac{x^{3}-3x+1}{x^{2}-x-2} \) into partial fractions, we first factor the denominator. The quadratic \( x^{2}-x-2 \) factors into \( (x-2)(x+1) \). Now we can express the original fraction as: \[ \frac{x^{3}-3x+1}{(x-2)(x+1)} = \frac{A}{x-2} + \frac{B}{x+1} \] where \( A \) and \( B \) are constants to be determined. Multiplying both sides by the denominator \( (x-2)(x+1) \), we have: \[ x^{3}-3x+1 = A(x+1) + B(x-2) \] Expanding the right side gives: \[ x^{3}-3x+1 = Ax + A + Bx - 2B = (A+B)x + (A-2B) \] Next, we equate the coefficients from both sides: 1. From the \( x^{3} \) term: There is no \( x^{3} \) term on the right, so we set the coefficient to 0. 2. From the \( x^{1} \) term: \( A + B = 0 \) 3. From the constant term: \( A - 2B = 1 \) Now, we can solve the system of equations: From \( A + B = 0 \), we get \( B = -A \). Substituting \( B = -A \) into \( A - 2B = 1 \) gives: \[ A - 2(-A) = 1 \implies A + 2A = 1 \implies 3A = 1 \implies A = \frac{1}{3} \] Thus, \( B = -\frac{1}{3} \). Now, substituting back into the partial fraction form: \[ \frac{x^{3}-3x+1}{(x-2)(x+1)} = \frac{1/3}{x-2} - \frac{1/3}{x+1} \] So, the partial fraction decomposition is: \[ \frac{x^{3}-3x+1}{x^{2}-x-2} = \frac{1/3}{x-2} - \frac{1/3}{x+1} \]

preguntas relacionadas

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Álgebra Mexico Feb 26, 2025
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad